The mutation of racism - Wieviorka, Michel (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
After the last war it would have seemed racism and antisemitism were called to disappear. But today they have come back and the history of their return can be traced back. Antisemitism would seem to have been relaunched as anticapitalism and as support in the fight for freedom of the palestinian people —or asenvy, mainly islamic, of today’s jews’ success in their settlement—. Racism on the other hand has suffered a transformation from the physical to the cultural and is activated today through discriminations launched on a planetary scale rather than coming from within the nations and is often connected with international tensions provoked by immigration. Finally racism is also taking shape in the need to rewrite the beginning and legitimations of the histories ofsuffering.
Keywords: New racisms; Antisemitism; Discrimination; Immigration